Memduh Şevket Esendal’ın hikayelerinde bürokrasi - Yıldırım, Emel İlhan (My University, 2013)
Sanatçı, siyasetçi, bürokrat, öğretmen, gazeteci olan Memduh Şevket Esendal(1883-1952) Türk tarihinin en önemli zaman diliminde yaşamış; Osmanlı İmparatorluğun çöküşüne ve Türkiye Cumhuriyeti’nin kuruluşuna tanıklık etmiştir. Yaşadığı dönemin önemli sosyal, siyasi ve kültürel olaylarına vâkıf olan Memduh Şevket Esendal siyasi, sosyal ve kültür hayatımızda yeri doldurulamayacak önemli bir aydınımızdır. Memuriyetin farklı kademelerinde bulunmuş, devletin kurumlarının işleyişine hâkim olan, gözlem gücüyle ve edindiği tecrübelerle eserlerinin içeriğini oluşturan Memduh Şevket Esendal’ın hikâyelerinde “bürokrasi” kavramı oldukça önemlidir. Bu tematik çalışmada Memduh Şevket Esendal’ın hikâyeleri bürokrasi başlığında incelenmiştir. Tezin Giriş bölümünde bürokrasi kavramının anlamı üzerinde durulmuş ve Memduh Şevket Esendal’ın bürokrasi ile ilişkisi, hayatı ve edebî kişiliği açıklanmıştır. Tezin ilk bölümünde bürokrasinin görüldüğü siyaset, eğitim, sağlık, askeriye, devlet daireleri alanları memuriyetteki işleyiş açısından ele alınmıştır. Tezin ikinci bölümünde memur ve bürokrat tipleri olumlu, olumsuz özellikleri ve özel hayatları yönüyle incelenmiştir. Tezin üçüncü bölümünde yöneten-yönetilen başlığında amir memur ilişkileri ve memuriyete bakış ele alınmıştır. Sonuç bölümünde Memduh Şevket Esendal’ın hikâyelerinde eleştirel bir bakış açısıyla ele aldığı bürokrasi temasıyla ilgili genel bir değerlendirme yapılmıştır. Bibliyografyada ise Memduh Şevket Esendal ve hikâyeleri ile ilgili kitap, tez ve makalelere yer verilmiştir. Ek bölümünde hikâyelerle ilgili yapılan tablo çalışmaları yer almaktadır. Memduh Şevket Esendal, bürokrasi, hikâye.

Memduh Şevket Esendal(1883-1952), who was a writer, a politician, bureaucrat, teacher and journalist, lived in the most significant period of the Turkish history; he witnessed the collapse of Ottoman Empire and foundation of the Turkish Republic. Memduh Şevket Esendal, who was aware of the social, politicial and cultural events of his period, was an irreplaceable intellectual in our social and cultural life. The term bureaucracy has a great importance in the works of Memduh Şevket Esendal,who served in various positions at government job and remained in possession of the operation of the state institutions and ,who formed the content of his works thanks to his observations and experiences. In this thematic study, stories of Memduh Şevket Esendal are examined under the heading of bureaucracy. In the introduction of the thesis, meaning of the bureaucracy is focused and Memduh Şevket Esendal’s relation with bureaucracy, his life and his literary personality are explained. In the first part of the thesis, the fields where bureaucracy was dominant such as politics, education, health, military and government offices are dealt in terms of operations of the state institutions. In the second part of the thesis, types of clerks and bureaucrats are examined with the aspects of pros, cons and finally with their private lives. In the third part of the thesis, relations between the superior and the subordinate officials and point of view for government job are examined under the heading of the managing and the managed classes. In the conclusion of the study, a general evaluation is made for the bureaucracy term which was covered with critical thinking in Memduh Şevket Esendal’s stories. Books, theses and articles based on Memduh Şevket Esendal and his works are given in bibliography. Chart studies about the stories are placed in the appendix. Key words: Memduh Şevket Esendal, bureaucracy, story.
Keywords: Esendal, Memduh Şevket, 1883-1952